Enforcement of anti-corruption legislation in Nigeria: an appraisal (2017)
The paper examines the meaning of corruption, its causes and dimensions within the Nigerian context. It also explores the legal framework targeted at combating the menace. It argues that though Nigeria has a wide array of laws in this area, corruption still flourishes in the country because the due implementation of the laws is being impeded by institutional and financial constraints as well as political and ethnic factors. Suggestions are preferred on how to successfully confront the menace and enhance the socio-economic development of the nation.